Is it time to shift towards multifactorial biotic stress in plant research? - Augusto B. Penteriche; Diego Z. Gallan; Marcio C. Silva-Filho (Plant Stress)
In natural and field environments, plants are simultaneously exposed to a diverse set of stressful conditions, like biotic and abiotic stressors, and must respond accordingly. These interactions result in intricate cross-talk between hormonal pathways, microbial communities, and volatile organic compounds (VOCs), shaping plant fitness and resistance mechanisms. Recent studies demonstrate that multifactorial stress combinations often trigger unpredictable transcriptional and metabolic responses, distinct from those induced by individual stressors alone. How multiple simultaneous or sequential biotic stresses affect plant fitness and defense, however, have been less reported. Climate change and extreme weather events are intensifying the likeliness that these conditions strike simultaneously or in close sequence, and increase the complexity of stress responses. Still, our knowledge on the mechanisms of plant defense to concomitant or sequential biotic stresses remains critically limited. Findings from unifactorial plant defense studies are often hindered in their precise extrapolation to complex, multifactorial natural environments. Thus, plant research urgently needs to consider multifactorial and combinatorial stressors, dynamic microbial interactions, and ecological trade-offs in plant stress adaptation. Resilient crop development and sustainable agriculture under global warming profoundly depend on our characterization of the complex mechanisms and cross-talks involved. We believe it is time for research to shift towards more complex, realistic stress scenarios to improve the applicability of findings and strengthen crop resilience amidst evolving agricultural demands.